2018
DOI: 10.2308/ogna-52163
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Findings from Single Audits: The Implications of Auditee Type and Auditor Expertise

Abstract: Single audits provide critical accountability for federal grant awards. Our study comprehensively examines differences in single audit findings (related to both financial statements and major program compliance) by auditee type (state/local government and nonprofit) and across varying levels of auditor expertise. In a sample of 24,144 audit engagements over the period 2004 through 2010, nonprofit auditees report fewer internal control deficiencies than government auditees, but more instances of questioned cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Despite the consistent goals of accountability and decreased audit burden, concerns with single audit quality have persisted over its 30-year history and significant evolution (e.g., AICPA 2017; GAO 1985GAO , 1986PCIE 2007;Tysiac 2017;Waymire et al 2018). Whether the new Uniform Guidance, which includes substantial changes from previous single audit guidance, will increase accountability and decrease burden remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the consistent goals of accountability and decreased audit burden, concerns with single audit quality have persisted over its 30-year history and significant evolution (e.g., AICPA 2017; GAO 1985GAO , 1986PCIE 2007;Tysiac 2017;Waymire et al 2018). Whether the new Uniform Guidance, which includes substantial changes from previous single audit guidance, will increase accountability and decrease burden remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, research has examined the association between single audit expertise by the audit firm conducting the audit and single audit findings. In a sample of approximately 24,000 single audits over the period 2004 through 2010, Waymire, Webb, and West (2018) find that firms with low single audit expertise (conducting ten or fewer single audits in one year) are associated with fewer compliance findings, after controlling for risk and other factors. Similarly, in a sample of 87 single audits with fiscal year-ends on or before November 30, 2015, the American Institute of Certified Public Accountants' (AICPA) peer review team found that audit quality is associated with the expertise of the firm conducting the audit, as well as membership in the AICPA's Governmental Audit Quality Center (GAQC) and qualifications of the engagement partner (AICPA 2017; Tysiac 2017).…”
Section: Introductionmentioning
confidence: 92%
“…The first is an indicator variable that is coded as one when a county was classified as a “low‐risk” auditee, zero otherwise. As part of the single audit procedure, an auditor can classify an auditee that satisfies certain criteria as a low‐risk auditee that requires “less audit effort” (López and Peters ; Peterson ; Rich and Zhang , 63; Waymire, Webb, and West ). The second is an indicator variable that is coded as one when a county received an unqualified audit opinion, zero otherwise (López and Peters ; Rivenbark, Roenigk, and Allison ).…”
Section: Model Specificationmentioning
confidence: 99%
“…The second is an indicator variable that is coded as one when an audit finds a material weakness and zero if the audit finding is either clean or a significant deficiency. The third is an ordinal variable coded as zero if the audit is clean, one if the audit finds a significant deficiency, and two if the audit finds a material weakness (López and Peters 2010;Peterson 2018;Rich and Zhang 2014;Waymire, Webb, and West 2018).…”
Section: Internal Control Deficiencies: the Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation